Tingkat Pengetahuan Pasien Rawat Jalan di RSUD dr. Gondo Suwarno Ungaran terhadap Kehalalan Obat - Martodihardjo, Suwaldi; Indriyati, Ajeng Mukti (Sultan Agung Islamic University of Semarang, 2024)
Background: Indonesia is a country where the majority of the population is Muslim. Ensuring the halalness of products, especially medicinal products in circulation, is a big concern for the government. For muslims consuming something halal is an obligation and command from Allah SWT, so that the halalness of a medicinal product becomes a necessity for consumers, especially muslim consumers. The purpose of this study is determine the level of knowledge of outpatients at RSUD dr. Gondo Suwarno Ungaran on halal medicine. Methods: This study using a cross sectional approach using a questionnaire that was announced to respondents. Results: The characteristics of respondents are divided into three they are, education, age and occupation. The majority of respondents are high school students (60%), age 18 years – 32 years (53.3%), with, private employee (36.7%). The level of patient knowledge of halal medicine (87.14%). Conclusion: Based on the research that has been conducted, it was found that the level of knowledge of outpatients at RSUD dr. Gondo Suwarno Ungaran on halal medicine 87.14% is included in the good category.